Upaya Meningkatkan Kompeteni Guru Kelas dalam Proses Pembelajaran Melalui Supervisi Akademik di Kelas Senyatanya SDN 41 Mataram - Aeni, Mar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this study is to determine the effectiveness of academic supervision in efforts to improve the competence of teachers Classroom in learning in the classroom, which benefits to the Head school is to know the improvement of teachers in the learning process. This study was conducted during two cycles, each cycle activity there are four stages of planning, implementation, observation, and reflection. The indicators of success in this study are; 1) the principal’s observation or teacher observation during the mentoring process has been successful score average> 4.0, 2) average teachers in the learning process reached> 85% with an average score> 70.00 (good category). Results research on first cycle principal principal observation (3.80), average teacher observation (3.33) and outcomes academic supervision in the average class (63.67). In cycle II the average principal’s observation (4.40) with percentage of achievement (100%), average teacher observation (4.33) with percentage of achievement (100%) and the results of academic supervision in the average class (81.22) with the percentage of achievement (100%). The success indicator has been reached, the research stated successful and the slowing in cycle II. Results research on the second cycle shows an increase in the competence of classroom teachers in the learning process real class It is recommended that other principals conduct similar research in an effort improving teacher competence, and for other classroom teachers to make the learning process appropriate with well-planned scenarios, responsibilities, backsliding improvement of learning achievement of learners in accordance with the class that is the responsibility.